Sistem Informasi Pendukung Keputusan Terhadap Mutu Lulusan dengan Metode Fuzzy Model Tsukamoto - Ghozali, Ahmad Lubis; Mustafid, Mustafid; Farikhin, Farikhin (Universitas Diponegoro, 2014)
The importance of graduate information systems to support leadership in taking a decision related to the development of alumni, so that should make for a graduate information systems implemented in the form of web portals. Analysis of the data processed by the method of OLAP (Online Analytical Processing), KPI (Key Performance Indicators) graduates, and data mining to extract and transform data holds the data will be stored in the warehouse. The process of data analysis using OLAP and Fuzzy method to determine the parameters of the model Tsukamoto graduate performance and quality of college graduates. The process of data analysis is represented in the form of tables, graphs, and dashboards, then used as a prop for academic results. OLAP analysis result data processed using the fuzzification, inference, and defuzzification to produce quality graduates index. These findings form a web-based information systems graduate portal with content features alumni and stakeholders as a graduate performance indicators that can be accessed through an Internet connection. The information system produces graduates index KPI performance and quality of graduates graduated as a decision support by the leadership and the head of the research program carried out at the University, KPI graduates to indicate that the parameters of the specific level of quality graduates and overall views of the dimensions of the year and course of study, such as in 2011 the level of quality of graduates of IT course overall